16 Foundation mentorship scheme pilot programme: is near-peer mentorship an effective way to look after incoming FY1s?. (3rd November 2019) - Srinivasan, Ananth; Tadros, Maria; Nelson, Isabel; Zimmerman, Mark; Haynes, Samuel; Ducksbury, Sigourney; Naqvi, Huma
Abstract : Background: Foundation Mentorship Scheme (FMS) is a near-peer lead programme developed by Foundation Year 2 (FY2) doctors for Foundation Year 1s (FY1s) as a pastoral adjunct to the education (ES) and clinical supervisor (CS) framework. Aims: FMS aims to provide a point of contact for FY1s; to bridge the gap between FY1s and ES/CS, troubleshoot on the shop-floor, help with e-portfolio and offer pastoral support. Methods: Mentors recruited from a pool of FY2s at a District General Hospital in Birmingham UK were matched in 1:4 groups with FY1s on concurrent rotations. Two meetings were undertaken per rotation, with further meetings as necessary. Quantitative Results were obtained using online surveys and qualitative feedback provided post-meetings. Results: FMS commenced 2 months into the first rotation with 33 FY1s. Thirteen (40%) FY1s engaged with the programme, ten (30%) opted out, four (12.5%) were unaware of the scheme. Five (16%) were unable to meet their mentors. 92% of engaging FY1s found the scheme useful, with 94% agreeing FMS would be invaluable if commenced earlier. The themes indicated FMS was most useful during the first rotation when FY1 learning curve is steepest; highly appreciated in surgical specialties; and effective in advising on e-portfolio. Other concerns included managing difficult colleagues; under-staffing; overstaying contracted hours; and teaching. Concerns were escalated appropriately to Foundation Programme leads. Conclusion: Challenges were encountered during scheme development. A significant proportion of FY1s opted out due to late commencement of the programme. Challenges coordinating across two hospital sites contributed to drop-outs. This scheme greatly benefited the engaging FY1s. To facilitate its success, FMS should be integrated with FY1 induction with protected time reserved for mentor meetings. Mentorship is a significant responsibility and formal training should be offered to mentors, especially in handling pastoral concerns.